“Rir para não chorar?” : relações étnico-raciais e seus significados nas construções identitárias de jovens negras/os e brancas/os no espaço escolar (2019-2020) - Santos, Fabrizzia Christiane dos (2021)
This summary is about a Master's research in Education, about black and white youths at school, which is linked to the Graduate Program in Education (PPGE) of the Federal University of Mato Grosso (UFMT), next to the Movements Research Line Social, Political and Popular Education and to the Center for Studies and Research on Race Relations and Education (NEPRE). The research object is the identity dynamics between black and white young people in a basic education school. Such an investigation is justified by the need to break the supposedly universal structures and epistemologies, because they affect unequally and disproportionately the bodies and lives of young black and white women. The objective is: to analyze the dynamics of identity among black and white youths from a state public school in the municipality of Várzea Grande / MT, considering the processes of (de) (re) construction of identities; understand the relational identity dynamics between black young people and between them and white girls; understand the identity processes of young white women and each other and of these young women with black women; and how these identities “become” at school. The research question asks what are the references, transmissions, practices and dialogues between black and white identities at school that allow processes of perception, interiorization and dissemination of identities? What categories are used to assert or impose, maintain and / or overcome hierarchical distinctions? As theoretical contributions of the research we understand the categories ethnic-racial relations, youth and anti-racist education from Paixão (2014), Fanon (2008), Hall (2013), Dayrell (2003), Sposito (2009), Bento (2014), Schucman (2014) Cavalleiro (2001), Gomes (2002), among others. We investigated this object using as a methodological procedure the qualitative research approach based on the Case Study method, whose instrument of data collection was constituted in the analysis of individual semi-structured interviews with managers, teachers, black and white young people. The research points out that the identities of black and white young people are constructed in the context of the school from the mechanisms of reproduction of racism, as well as points to ways of overcoming this, especially by bringing young people as subjects who think and act on this reality. We identified that “psychological lynchings” were the most recurrent expressions of racism at school, as well as the silencing processes of contributions and black identities. On the other hand, whiteness proved to be a denied identity, precisely to hide the other side of this ethnic-racial relationship, this time in the position of those who benefit in terms of racial privileges. In view of the investigated, we understand that anti-racist education is necessary from the commitment of white and black people, where the institutional role of the school in the denaturalization of a racially stereotyped vision about blackness and whiteness stands out.